Prove that the following two equations represent the simple harmonic motion-
X = A cosωt + B sinωt
X = A eiωt
The equation of harmonic oscillations is "x(t)=A'\\sin(\\omega t+\\phi)" or "x(t)=A'\\cos(\\omega t+\\phi)" . So,
a) "x(t)=A'\\sin(\\omega t+\\phi)=A'(\\sin\\omega t\\cdot\\ \\cos\\phi+\\cos\\omega t\\cdot \\sin\\phi)="
"=A'\\sin\\omega t\\cdot\\ \\cos\\phi+A'\\cos\\omega t\\cdot \\sin\\phi=B\\sin\\omega t+A\\cos\\omega t="
"=A\\cos\\omega t+B\\sin\\omega t" . Proved
b) For the simple harmonic motion
"\\frac{d^2x(t)}{dt^2}+x(t)\\omega^2=0"
"x(t)=Ae^{i\\omega t}"
"-A\\omega^2e^{i\\omega t}+Ae^{i\\omega t}\\omega^2=0" . Proved
Comments
Leave a comment